Design of Cobalt-Free Ni-Rich Cathodes for High-Performance Sodium-Ion Batteries Using Electrochemical Li+/Na+ Exchange - Yao Lv; Liqiu Shi; Jianfeng Yu; Shifei Huang (Energies, 2025)
Sodium-ion batteries are renowned for their abundant reserves, cost-efficiency, safety, and eco-friendliness and are prime candidates for large-scale energy storage applications. The development of cathode materials plays a crucial role in shaping both the commercialization path and the ultimate performance capabilities of SIBs. To overcome the intricate synthesis challenges associated with pure-phase sodium-ion cathode materials, this study introduces an innovative and streamlined electrochemical Li+/Na+ exchange process, successfully fabricating a high-capacity Ni-rich cathode material. This cathode material boasts a remarkable reversible capacity of 180 mAh g−1 at 0.1 C and retains a high-rate capacity of 115 mAh g−1 even at 5 C. Additionally, it exhibits exceptional cycling stability, retaining about 85% of its capacity at 1 C after 50 cycles and still maintaining a capacity greater than 60% after 100 cycles. The Na-NMA85 full cell preserves a discharge capacity of 110 mAh g−1 after 100 cycles, with a capacity retention rate of 80%. This research underscores innovative strategies for designing ion-intercalation-based cathode materials that enhance battery performance, providing fresh perspectives for advancing high-performance battery technologies.